Pengaruh Online Customer Review dan Online Customer Rating terhadap Keputusan Pembelian Skincare di Marketplace Shopee: Survei pada Mahasiswa Ilmu Komunikasi UMJ Angkatan 2020-2021 - Adinda Chaerani; Jaimiaiti KN (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
Technological developments have changed consumer behavior from shopping through offline stores to online stores or online shopping. These changes affect consumer purchasing decisions when buying a product. This makes the study of e-commerce an interesting subject of study in today's world. The purpose of this study is to hopefully provide an overview of current online customer behavior and can be used to determine online marketing strategies. The population in this study were 234 people who were students of FISIP UMJ Class of 2020 & 2021. The sampling technique used Simple Random Sampling with a total of 67 samples. The data obtained was then analyzed by multiple linear regression analysis using IBM SPSS.25 software. Based on the results of statistical testing, it shows that the Online Customer Review variable has a tcount value of 10.612> 1.997 and a significant value of 0.000 <0.05 and Online Customer Rating has a tcount value of 6.997> 1.997 and a significant value of 0.000 <0.05 so that Ho is rejected Ha is accepted, it can be concluded that Online Customer Review and Online Customer Rating have a positive and significant influence on Purchasing Decisions. The influence of Online Customer Rating on Purchasing Decisions.